Stick tool use by chimpanzees in a forest fragment in Uganda’s Budongo-Bugoma corridor: preliminary observations from Kasongoire - Aimee Oxley; Balinda Kiiza Jovan (Revue de Primatologie)
Chimpanzees are well-known tool users, with differences reported in the tool use repertoires among communities and subspecies. Chimpanzees at most study sites exhibit some degree of stick tool use behaviour for extractive foraging, with the exception of eastern chimpanzees (Pan troglodytes schweinfurthii) inhabiting Budongo Forest in western Uganda. Chimpanzees there have never been observed using stick tools despite being studied for decades, although, more recently, probing and digging tool use has been documented in neighbouring forest fragments. Here, I report preliminary observations of immature chimpanzees using stick tools as probes in a foraging context in Kasongoire, a newly studied community in the unprotected forest fragments outside Budongo Forest. The behaviour appears to be rare and insect prey seems not to have been actually ingested, but the observations provide further evidence of probing stick tool use by chimpanzees only 15 km from the main forest block. Differences in tool use have been previously reported between neighbouring communities of chimpanzees. Considering the complete absence of stick tool use in Budongo Forest, the increasing evidence that it is present in such close geographical proximity poses questions about the transfer of cultural knowledge between individuals and communities.